A prototype of a low-cost autonomous mini-vehicle - Gabriel Arthur Vicentini; Luan Gabriel Vidal da Silva; Carlos Dias da Silva Junior; Elias José de Rezende Freitas (The Journal of Engineering and Exact Sciences)
This work presents the first phase of developing a prototype of an autonomous mini-vehicle on a scale of 1:24. The main contribution is the feasibility and executability of the project using only simple, readily available, and low-cost components. The primary focus was to construct a functional 3D chassis capable of housing all the necessary parts, creating full-scale 3D mechanical components. In addition, we show the first server-client programming using the ROS (Robot Operating System) platform, which allows communication between a central computer and the ESP32 microcontroller. All data that supports this paper are freely available.